(x/x+1)+5/8=5/2(x+1)+3/4

Simple and best practice solution for (x/x+1)+5/8=5/2(x+1)+3/4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x/x+1)+5/8=5/2(x+1)+3/4 equation:


(x/x+1)+5/8=5/2(x+1)+3/4

We simplify the equation to the form, which is simple to understand
(x/x+1)+5/8=5/2(x+1)+3/4

Remove unnecessary parentheses
+2 + 0.625=+2.5*(x+1) + 0.75

Reorder the terms in parentheses
+2 + 0.625=+(+2.5x+2.5) + 0.75

Remove unnecessary parentheses
+2 + 0.625=+2.5x+2.5 + 0.75

We move all terms containing x to the left and all other terms to the right.
-2.5x=+2.5 + 0.75-2-0.625

We simplify left and right side of the equation.
-2.5x=0.625

We divide both sides of the equation by -02.5 to get x.
x=-0.25

See similar equations:

| 5/6a-10=1/3a-14 | | 14(2x+20)= | | 2a+6-10a= | | =25n-10+3-8 | | 7.5=3+x/2 | | 24a+72b+40c= | | 5(w+10)+2x+3(2x)=700 | | 7x+4=4(x-11) | | (4*r)*13= | | 7y-12y+3y= | | 4(8+m)=2m+16 | | 4+7=(3-9v) | | lnx^5/2-0.5lnx=ln25 | | 15c+7=11c+35 | | -5(-4+9x)= | | 7r=2(4r-9) | | (9y/14)/(6/14) | | -7(x+1)+7(7+x)= | | 2x+(2x-8)=72 | | X-7/8=-7/12 | | X(-2x+5)=33 | | 6m-3=1/3m | | -15=(3n/5) | | X-7/8=7/12 | | 48x-4=13x+6 | | -7+6p=-97 | | X+x+(x-4)+(x-4)=72 | | -(2r+7s)+2(r+s)= | | 12/6*5 | | x-1.6=-2.5 | | -6(a-3)-7(5-4a)= | | 1/42/7 |

Equations solver categories